2014
DOI: 10.1261/rna.043984.113
|View full text |Cite
|
Sign up to set email alerts
|

A conserved role for the zinc finger polyadenosine RNA binding protein, ZC3H14, in control of poly(A) tail length

Abstract: The ZC3H14 gene, which encodes a ubiquitously expressed, evolutionarily conserved, nuclear, zinc finger polyadenosine RNAbinding protein, was recently linked to autosomal recessive, nonsyndromic intellectual disability. Although studies have been carried out to examine the function of putative orthologs of ZC3H14 in Saccharomyces cerevisiae, where the protein is termed Nab2, and Drosophila, where the protein has been designated dNab2, little is known about the function of mammalian ZC3H14. Work from both buddi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 62 publications
(120 citation statements)
references
References 34 publications
11
109
0
Order By: Relevance
“…The functions of Nab2 homologs in these diverse organisms also seem to be conserved: Poly(A) binding has been shown in H. sapiens, M. musculus, R. norvegicus, and D. melanogaster (Pak et al 2011;Kelly et al 2014), and its requirement for correct poly(A) tail length has been shown in D. melanogaster and probably H. sapiens (Pak et al 2011). Human ZC3H14 is ubiquitously expressed and exists in four different splice variants: Isoforms 1, 2, 3, and 3short contain a predicted classical nuclear localization signal (cNLS) and localize to the nucleus, whereas isoform 4 contains an alternative first exon lacking the NLS and consequently localizes to the cytoplasm (Leung et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The functions of Nab2 homologs in these diverse organisms also seem to be conserved: Poly(A) binding has been shown in H. sapiens, M. musculus, R. norvegicus, and D. melanogaster (Pak et al 2011;Kelly et al 2014), and its requirement for correct poly(A) tail length has been shown in D. melanogaster and probably H. sapiens (Pak et al 2011). Human ZC3H14 is ubiquitously expressed and exists in four different splice variants: Isoforms 1, 2, 3, and 3short contain a predicted classical nuclear localization signal (cNLS) and localize to the nucleus, whereas isoform 4 contains an alternative first exon lacking the NLS and consequently localizes to the cytoplasm (Leung et al 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recent work on D. melanogaster Nab2 (dNab2) provides evidence for the critical role of this protein in neurons. Re-expression of dNab2 specifically in the neurons of dNab2 null flies rescues developmental and locomotor defects observed in these mutant flies (12,31). Importantly, in a trans-species rescue experiment, the nuclear isoform of ZC3H14, isoform 1, but not the cytoplasmic isoform 4, can also rescue dNab2 mutant phenotypes, providing evidence for the critical function of ZC3H14 in neurons (12,31).…”
Section: Zc3h14 Ensures Proper Processing Of Atp5g1 Pre-mrnamentioning
confidence: 80%
“…Extensive biochemical studies demonstrate that ZC3H14/ Nab2 binds polyadenosine RNA with high affinity (15) and plays an evolutionarily conserved role in poly(A) tail length regulation (12,24,31), supporting a model where ZC3H14 likely binds to the poly(A) tails added to virtually all mRNA transcripts. However, the results from our microarray analysis suggest that ZC3H14 could regulate specific mRNA targets in MCF-7 cells.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations